An Intracellular Tripeptide Arg-His-Trp of Serum Origin Detected in MCF-7 Cells is a Possible Agonist to β2 Adrenoceptor - Chandore, Hritik; Raj, Ajay K.; Lokhande, Kiran Bharat; Swamy, Krishna Venkateswara; Pal, Jayanta Kumar; Sharma, Nilesh Kumar (Protein and Peptide Letters, 2021)
Background: The need for agonists and antagonists of β2 adrenoceptor (β2AR) is warranted in various human disease conditions, including cancer, cardiovascular and other metabolic disorders. However, the sources of agonists of β2AR are diverse in nature. Interestingly, there is a complete gap in the exploration of agonists of β2AR from serum that is a well-known component of culture media that supports growth and proliferation of normal and cancer cells in vitro. Methods: In this paper, we employed a novel vertical tube gel electrophoresis (VTGE)-assisted purification of intracellular metabolites of MCF-7 cells grown in vitro in complete media with fetal bovine serum (FBS). Intracellular metabolites of MCF-7 cells were then analyzed by LC-HRMS. Identified intracellular tripeptides of FBS origin were evaluated for their molecular interactions with various extracellular and intracellular receptors, including β2AR (PDB ID: 2RH1) by employing molecular docking and molecular dynamics simulations (MDS). A known agonist of β2AR, isoproterenol was used as a positive control in molecular docking and MDS analyses. Results: We report here the identification of a few novel intracellular tripeptides, namely Arg-His- Trp, (PubChem CID-145453842), Pro-Ile-Glu, (PubChem CID-145457492), Cys-Gln-Gln, (PubChem CID-71471965), Glu-Glu-Lys, (PubChem CID-11441068) and Gly-Cys-Leu (PubChem CID-145455600) of FBS origin in MCF-7 cells. Molecular docking and MDS analyses revealed that among these molecules, the tripeptide Arg-His-Trp shows a favorable binding affinity with β2AR (-9.8 Kcal/mol). The agonistic effect of Arg-His-Trp is significant and comparable with that of a known agonist of β2AR, isoproterenol. Conclusion: In conclusion, we identified a unique Arg-His-Trp tripeptide of FBS origin in MCF-7 cells by employing a novel approach. This unique tripeptide Arg-His-Trp is suggested to be a potential agonist of β2AR and it may have applications in the context of various human diseases like bronchial asthma and chronic obstructive pulmonary disease (COPD).
Keywords: molecular dynamic simulations